Toward a head movement‐based system for multilayer digital content exploration. (30th November 2020) - Bruno, Alessandro; Moore, Morgan; Zhang, Jinglu; Lancette, Stéphane; Ward, Ville P.; Chang, Jian
Abstract: In this article, we propose a novel technique based on Head Movement tracking to explore multilayer digital content. We extend an existing method by Kazemi et al. dealing with the extraction of facial landmarks to define the "head‐gaze" of the user. We use the "head‐gaze" to calculate the users' on‐screen coordinates. Hovering the cursor over an interactive area for a given time threshold allows users to explore the next layer contents. Our experimental sessions allowed us to measure the technique's level of control and usability. Our results were promising, and users were able to interact with considerably small regions. Furthermore, our lightweight method can be used with a low‐cost camera or webcam and a wide range of screen sizes and distances. Abstract : We propose a novel technique based on head movement tracking to explore multilayer digital content. Facial landmarks are used to define the "head gaze" of the user and project the "head‐gaze" coordinates as a cursor onto the screen. Hovering the cursor over an interactive area for a given time threshold allows users to explore the next layer contents. The experimental setup allows the method to achieve a certain level of stability and easiness in the control of the cursor. In greater detail, subjects who took part in experiments were able to hover the cursor over small regions just by using their head movements. Furthermore, the method relies on lightweight functions and a low‐cost camera or webcam and can run on a wide range of screen sizes.